2021
DOI: 10.1037/xap0000337
|View full text |Cite
|
Sign up to set email alerts
|

“Only your first yes will count”: The impact of prelineup instructions on sequential lineup decisions.

Abstract: When administering sequential lineups, researchers often inform their participants that only their first yes response will count. This instruction differs from the original sequential lineup protocol and from how sequential lineups are conducted in practice. Participants (N = 896) viewed a videotaped mock crime and viewed a simultaneous lineup, a sequential lineup with a first-yes-counts instruction, or a sequential control lineup (with no first-yes-counts instruction); the lineup was either target-present or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 58 publications
(136 reference statements)
4
41
0
Order By: Relevance
“…A superiority of sequential lineups has been postulated based on the diagnosticity ratio 44 which, however, has been criticized for confounding the ability to distinguish between a culprit and an innocent suspect and response bias 20 . SDT-based analyses have sometimes shown equivalent performance of simultaneous and sequential lineups 13 , 37 , 39 , 47 , 83 , 84 and sometimes a superiority of simultaneous over sequential lineups 11 , 38 , 62 , 85 88 . In all experiments reported here, the estimates of the culprit-presence detection parameter dP were slightly but consistently higher in the simultaneous-lineup conditions than in the sequential-lineup conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A superiority of sequential lineups has been postulated based on the diagnosticity ratio 44 which, however, has been criticized for confounding the ability to distinguish between a culprit and an innocent suspect and response bias 20 . SDT-based analyses have sometimes shown equivalent performance of simultaneous and sequential lineups 13 , 37 , 39 , 47 , 83 , 84 and sometimes a superiority of simultaneous over sequential lineups 11 , 38 , 62 , 85 88 . In all experiments reported here, the estimates of the culprit-presence detection parameter dP were slightly but consistently higher in the simultaneous-lineup conditions than in the sequential-lineup conditions.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in many previous studies the only-the-first-yes-counts rule was used. Horry et al 62 have demonstrated that only-the-first-yes-counts instructions systematically reduce the rate of positive identifications in sequential lineups by discouraging participants from guessing. This is plausible at a psychological level: participants may well shy away from using their only identification option when they cannot know, at the time of their decision, whether better options will follow.…”
Section: Discussionmentioning
confidence: 99%
“…Meissner et al (2005) reported a decrease in diagnosticity as more fillers are added to a lineup; however, they did not detect an interaction with the mode of lineup presentation. These conflicting findings may have been a consequence of how the sequential lineups were operationalized in the experiments, as the methodologies were all quite different and there are many sequential lineup features that could interact with lineup size, such as the prelineup instructions, the suspect’s position, and the stopping rule (Horry et al, 2020; Steblay et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be that there is, as argued by Horry et al (2021), a dynamic criterion shift which reduces the conservative criterion of listeners as the parade progresses.…”
Section: Discussionmentioning
confidence: 99%